NILAI-NILAI TASAWUF DALAM KUMPULAN LAYANG-LAYANG KENANGAN KARYA DEDEN SUGANDA SEBAGAI PEMBELAJARAN BERBASIS KARAKTER: NILAI-NILAI TASAWUF PADA KUMPULAN PUISI LAYANG-LAYANG KENANGAN - Faisal Kemal; Prima Gusti Yanti; Ahmad Sulton Ghozali (Jurnal Semantik, 2024)
This study describes the values of Sufism found in the poem "Kites of Memories" into character education in junior high school (SMP). The method used is qualitative-descriptive, with a focus on interpreting the values of Sufism in the poetry of Deden Suganda. The results of this study identify repentance, wara, zuhud, gratitude, ma'rifat, mahabbah, qurb, muraqabah, and al-uns as implied values. The purpose of applying these values is to strengthen students' self-awareness of their potential and weaknesses. This research has significant implications in character education by integrating spiritual and introspective dimensions into the curriculum. Literature containing Sufi values provides deep character learning, allowing students to understand Islamic teachings through the experience of reading poetry. Additionally, this research provides insights into the essence of life and achieving inner peace through practical application of Sufi values. The results can serve as a guide for educators to implement Sufi values, enrich character education in SMP, and contribute to understanding the relationship between literature and spiritual dimensions, paving the way for a holistic and meaningful educational approach.